Clear cell sarcoma of the kidney in a 62-year-old patient presenting with generalized pruritus - Zhang, Yuxi (BMC Cancer, 2019)
BACKGROUND: Clear cell sarcoma of the kidney (CCSK) is the second most common renal tumor in children following Wilms’ tumor. CCSK is extremely rare in adults, with only 25 adult cases reported in the medical literature. CASE PRESENTATION: We reported a 62-year-old man with a right renal mass presenting only with generalized pruritus who underwent radical right nephrectomy. With immunostaining, tumor cells were positive for expressed vimentin, neural cell adhesion molecule (NCAM, CD56), and Ki-67 and focally positive for p53, CD10 and Bcl-2. The histopathological diagnosis was CCSK. Two weeks after the operation, the generalized pruritus ended. One month after the operation, the patient started treatment with a regimen combining doxorubicin, vincristine, cyclophosphamide, and etoposide. At the 20-month follow-up visit, there was no evidence of local recurrence or metastases. CONCLUSIONS: In a patient presenting with generalized pruritus, further evaluation for an underlying malignancy should be considered. It is difficult to distinguish CCSK from undifferentiated renal neoplasms. Immunohistochemistry could help to make exact histopathological diagnoses. The BCL-6 corepressor (BCOR) gene could play a significant role in CCSK tumorigenesis and be a good marker for CCSK diagnosis. Surgery with combination chemotherapy and radiation therapy could be used to treat CCSK in older patients.